Purification and characterization of Phoenix dactylifera lectin: µ-Opioid receptor-mediated antinociceptive and gastroprotective activities - Sara A.A. Elmubarak; Maha B. Dafalla; Ahmed H. Idries; Eva H. Naser; Yusria E. Abdelrahim; Entsar A. Abdalrhman; Bashir M. Ahmed; Makarim Elfadil M. Osman; Amna K.E. Awadalla; Reem M.A. Ebrahim; Ashraf O. Abdellatif; Haseeba A. Saad; et al. (Phytomedicine Plus)
Phoenix dactylifera (date palm) holds significant medicinal value, particularly in traditional medicine. This study focuses on purifying and characterizing a lectin (PdSL) extracted from its seeds and assessing its physicochemical stability, glycoprotein nature, and therapeutic properties, including analgesic and gastroprotective activities. PdSL was extracted via phosphate-buffered saline (PBS) and purified via ion exchange and affinity chromatography, resulting in a twofold increase in purity. Stability tests included varying temperatures (40–100 °C), pH levels (2–13), and exposure to denaturing agents. Biological assays were used to evaluate its analgesic effects in thermal (hot plate, p < 0.05) and chemical (acetic acid writhing, p < 0.01) pain models. Gastroprotective activity was assessed in an ethanol-induced gastric ulcer model in rats, with statistical significance at P < 0.05. PdSL demonstrated exceptional stability, retaining activity across a broad range of temperatures (up to 100 °C) and pH values (5.5–9.5). The lectin maintained hemagglutination activity under challenging conditions and showed specificity for sheep erythrocytes and mannose-binding properties. It was identified as a glycoprotein with 37.64 % neutral sugars and exhibited a hydrophobic binding site for adenine. In analgesic assays, PdSL significantly increased the pain threshold in the hotplate test, particularly at 6 mg/kg after 60 mins (p < 0.003), and in the writhing test, with a dose-dependent pain inhibition of 80–89 % (p < 0.01). Gastroprotective activity revealed dose-dependent ulcer inhibition, with a maximum reduction of 89 % at 1 mg/kg (p < 0.0001), along with normalization of the gastric pH. PdSL from Phoenix dactylifera seeds exhibits remarkable stability and therapeutic efficacy, including pain-relieving and antiulcer activities, with statistically significant results highlighting its potential as a candidate for drug development. These findings encourage further exploration of plant-derived lectins in biomedical research.